Implementation assessment in confidential enquiry programmes: A scoping review. - Jayakody, H; Knight, M (Wiley, 2019)
Background Response should be a key part of maternal death surveillance and response (MDSR) programmes, which include confidential enquiries into maternal deaths. The programmes investigate avoidable factors in maternal deaths and make recommendations for improving maternity care. There is a gap in information on how these recommendations are transformed into practice.